Penyelenggaraan Pemerintahan Desa Berbasis Kolaboratif - Muh.Alfian Fallahiyan; Ashari Ashari; Agung Setiawan; Rahmadani Rahmadani; Riska Ari Amalia (LPPI UMN AL WASHLIYAH, 2025)
The village is the smallest governmental organization that possesses autonomy in managing its governance, commonly referred to as village autonomy. This autonomy serves as a means for all components involved in village governance—both the village government and other community elements—to synergize in implementing development within the village. However, at present, village governance is not yet fully carried out in synergy with all elements within the village. This situation underlies our initiative to conduct outreach on the importance of synergy or collaboration in the implementation of village governance. Our activities were carried out through lectures, discussions, and legal consultations. Based on the outreach we conducted, village governance, particularly in Sembalun Village, has not been collaborative. This is due to a lack of understanding among the components of village governance regarding the duties and roles of the community as part of the governance system, including the various forms of participation they can offer. Therefore, we provide recommendations based on our outreach, suggesting that all forms of governmental and developmental activities in the village should involve community participation in their implementation.